2015
DOI: 10.1016/j.ssci.2014.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Perceived risks for slipping and falling at work during wintertime and criteria for a slip-resistant winter shoe among Swedish outdoor workers

Abstract: The leading cause of work related accidents in Sweden is falls. Many slips and falls occur on icy and snowy surfaces, but there is limited knowledge about how to prevent accidents during outdoor work in winter conditions. The purpose of this study was to describe risk factors of slips and falls and criteria for slip-resistant winter shoes from a user perspective. The result is based on focus group interviews with 20 men and women working in mail delivery, construction and home care in Sweden. The data was anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 41 publications
0
11
0
2
Order By: Relevance
“…Despite the limitations of previous research, material hardness, or cushioning, has been identified as a dominant factor influencing footwear comfort in running and military populations [ 5 , 12 , 13 ]. Qualitative research with working populations, including those undertaking prolonged standing, identify self-reported links between footwear comfort and footwear cushioning [ 1 , 2 ], suggesting that material hardness is also important for these populations. Although softer insoles have been associated with greater comfort scores [ 10 , 11 ], insoles rated as less comfortable by the majority are still the preferred choice for other individuals [ 4 , 5 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the limitations of previous research, material hardness, or cushioning, has been identified as a dominant factor influencing footwear comfort in running and military populations [ 5 , 12 , 13 ]. Qualitative research with working populations, including those undertaking prolonged standing, identify self-reported links between footwear comfort and footwear cushioning [ 1 , 2 ], suggesting that material hardness is also important for these populations. Although softer insoles have been associated with greater comfort scores [ 10 , 11 ], insoles rated as less comfortable by the majority are still the preferred choice for other individuals [ 4 , 5 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is recognized that slips and falls are often attributed to slippery surfaces, in other words they have low friction properties [7]. In wintertime, there are various types of underfoot surfaces such as ice, snow, melting ice or/snow, compressed snow, ice covered with snow [37] and thus the degree of slipperiness will differ depending on the surface temperature, structure, hardness and thickness of the water layer [8].…”
Section: Introductionmentioning
confidence: 99%
“…In Finland, snowy or icy ground surface conditions can be rather hazardous to human health during wintertime. Studies in ergonomics have shown that slip-and-fall accidents occur more often during the winter months [ 7 , 8 , 9 ] and it is not only outdoor workers but also the general public that suffer an elevated risk of slipping and falling [ 8 ]. Berggård [ 9 ] has estimated that “more than 100,000 pedestrians in the Nordic countries are every winter expected to receive medical treatment due to winter weather and slippery conditions”.…”
Section: Introductionmentioning
confidence: 99%
“…Alguns trabalhos na Antártica requerem precisão motora fina e, às vezes, é preciso tirar as luvas, o que pode provocar queimaduras pelo frio. Um estudo no Ártico (Norlander, Miller, & Gard, 2015) indicou a urgência de investimentos em equipamentos de proteção individual, o que tende a evitar acidentes, como escorregões, ou congelamentos. Destaca-se que as vestimentas nem sempre são apropriadas para a locomoção ou manuseamento de instrumentos e exigem sincronismo entre ações em nível logístico e operacional.…”
Section: Estressores Ocupacionaisunclassified